PENERAPAN PIRING MAKAN MODEL T DAN EDUKASI AKTIVITAS FISIK PADA KELUARGA DENGAN REMAJA OBESITAS - Aulia Angelina Muhtarini Cahyaningtyas; Titih Huriah (Jurnal Ilmiah Keperawatan, 2023)
Background: Obesity is a global health issue that has been designated by the WHO as a global epidemic that requires prompt treatment. Adolescent obesity is typically caused by an imbalanced diet and a lack of physical activity. According to 2016 data, 39% of adults aged 18 and older are overweight (39% males and 40% women). Setting a diet based on the Model T dinner plate concept can aid in balanced nutrition. This study aims to see how effective the T-style plate and physical activity education are in dealing with the problem of adolescent obesity. Method: This is a descriptive study that employs a case study approach. Nursing care was provided for two weeks, with the intervention utilizing the T-style meal plate and physical activity education delivered in three meetings. Results: The case study revealed weight loss after three times interventions, with the client's weight being 117 kg before the intervention and 116.4 kg after the intervention. Conclusion: The case study concluded that using the T plate model and physical activity instruction can decrease client weight and raise knowledge and behavior regarding physical activity, both of which can improve health.